Pengaruh disipln kerja, motivasi dan kompensasi terhadap kinerja karyawan PT Excelitas Technologies Batam - Fathin, Lina Nur; Wasiman (SCIENTIA JOURNAL, 2022)
Human resources are factors that need to be considered by a company. Human resources are a driving tool to be able to run a company and as an asset for the survival of the company both in the short and long term. All companies certainly have the same goal, namely to achieve a profit and have a very small risk of loss. In order to achieve this goal, a company needs to maximize the use of production and non-production factors such as capital, labor, worker skills, technology and other factors. Of all these factors, it is an important factor, but the most important factor is human resources, namely workers, if there are no workers, then no one runs the company. In this study using a descriptive research design and a quantitative approach. The application used to assist in this research is SPSS version 25. The sample used is 120 respondents with a random sampling system. Data collection is done by distributing questionnaires. Based on the results of statistical tests, it is known that the variables of work discipline, motivation, compensation and employee performance are normally distributed, in which the independent variables do not occur multicollinearity and heteroscedasticity. The results of the t test show that the work discipline variable has a positive and significant effect on employee performance, the motivation variable has a positive and significant effect on employee performance, while the f test results simultaneously state that work discipline, motivation, and compensation variables have a significant effect on employee performance.